Sociocultural adaptation challenges of international students at a higher learning institution in Malaysia - GulRaihan, GulRaihan (Penerbit UTM Press, 2017)
Malaysian Higher Learning Institutions currently have more than one hundred thousand international students as a part of its pledge of internationalization of Higher Education. One of the core challenges for its international students is their sociocultural adjustments into the new environment. This study investigates the sociocultural adaptation challenges of international students in the host university. A total of 200 students were surveyed using a modified version of the sociocultural adaptation scale (SCAS). Using a quantitative approach, Exploratory Factor Analysis, ANOVA and T-test were performed to analyze the data. The findings show that the students face challenges in four aspects, namely language proficiency, academic adaptation, environmental adaptation and interpersonal adaptation. The results of the independent sample t-test show that, ‘language adaptation’ and ‘academic adaptation’ have more influence on the sociocultural adjustments of international students, while ‘interpersonal adaptation’ has little influence. In addition, results of the ANOVA show that the university campus and region of origin of the students influence the ‘academic and ‘environmental’ adaptation of the students. Based on the findings, we suggest that Malaysian universities should encourage cross-cultural adaptation through improving their social support linkages with the locals and the people of different culture than their own.